Two-dimensional magnetic micro-module reconfigurations based on inter-modular interactions. (April 2013) - Miyashita, Shuhei; Diller, Eric; Sitti, Metin
We present a scheme of two-dimensional module reconfiguration based on interactions between microscale magnetic modules with potential applications in micro-robotics, particularly in automatic micro-fabrication, non-invasive diagnoses, micro-surgery, and drug delivery at unreachable sites. The approach taken is a mixture of a top-down engineering approach and a bottom-up self-assembly approach, where reconfiguration commands are delivered from outside the workspace in the form of a magnetic field, which directs configuration changes in the set of modules by changing the strengths of individual magnetic moments. The magnetic modules in the study, 750μm in size, are constrained to a liquid surface, providing a simplified two degrees of freedom translational motion environment, where the laterally interacting inter-module magnetic force determines the assembly configuration. In this way, the relative distance of the magnets simply reflects the strength of the interactions, and thus easily enables the design of the system's reconfiguration scenario. Reconfiguration occurs when the magnetic attractive forces are changed. To direct the assembly morphology in a controlled manner, the modules are addressed magnetically by incorporating a different magnetic material into each module type, each with different magnetic hysteresis characteristics. For addressing different modules' magnetizations, we incorporate three different magnetic materials that feature different magnetic coercivities. This allows for the independent control of the magnetization of each material using applied external fields of varying strength, leading to arbitrary configuration change in a three-module set and limited control over a four-module set. General cases with more than five modules are further discussed.